(untitled) (IMC Journal of Medical Science, 2020)
Background and aims: Hypothyroidism is a common global endocrine disorder. The magnitude of hypothyroidism at community level in Bangladesh is unknown except some clinic-based studies. The present study was undertaken to determine the prevalence of hypothyroidism in different occupational groups of Bangladeshi population and to assess the risks related to it. Study design: Three occupational groups (house-wives, college students, rickshaw-pullers) of native Bangladeshi population were purposively selected. Investigations included socio-demography, anthropometry, blood pressure and biochemistry [fasting blood glucose, lipids, thyroid stimulating hormone (TSH) and free thyroxin (FT4)]. Laboratory tests were done only on a randomized sample of participants. Results: Overall, 626 (M/F=123 / 503) participants with a mean age of 35.9 (34.75 – 37.02) years volunteered. The mean values of all participant for TSH and FT4 were 2.08 (95%CI: 1.72 – 2.45) μiu/ml and 13.04 (95CI:12.86 – 13.22) pmol/L respectively. The third percentile of TSH ranged from 0.42 to 0.46 μiu/ml and 97th percentile ranged from 5.16 to 5.24 μiu/ml. For FT4, the 3rd and the 97th percentile were 10.3 and 16.41 pmol/L, respectively. The prevalence of hypothyroidism in both sexes was 7.0% (M/F=4.1/8.3%). Occupational groups, sex and increasing age, obesity, blood pressure, and lipids showed no association with hypothyroidism. Hyperglycemia was proved to be a significant risk for hypothyroidism (prevalence in diabetic vs. non-diabetic was12.9% vs. 5.5%, p = 0.04; FBG was correlated with TSH, r = 0.138, p <0.001). Conclusions: It is concluded that the prevalence of hypothyroidism was almost equal to other studies. Hypothyroidism was not related to increasing age, obesity, blood pressure and lipids. It was found to affect all sexes, all social classes and all occupational groups. Hyperglycemia was evidently found as significant risk for hypothyroidism. Ibrahim Med. Coll. J. 2019; 13(2): 9-17